Isolation and molecular characterization of the [Fe]-hydrogenase from the unicellular green alga Chlorella fusca - Winkler, M.;Heil, B.;Heil, B.;Happe, T.
[Fe]-hydrogenases are redoxenzymes that catalyze the reversible reduction of protons to hydrogen. Hydrogenase activity was observed in a culture of the unicellular green alga Chlorella fusca after an anaerobic incubation, but not in the related species Chlorella vulgaris. Specific polymerase chain reaction (PCR) techniques lead to the isolation of the cDNA and the genomic DNA of a special type of [Fe]-hydrogenase in C. fusca. The functional [Fe]-hydrogenase was purified to homogeneity and its N-terminus was sequenced. The polypeptide sequence shows a high degree of identity with the amino acid sequence deduced from the respective cDNA region. Structural and biochemical analyses indicate that ferredoxin is the main physiological electron donor. D 2002 Elsevier Science B.V. All rights reserved.
Artículo
Keywords: CHLORELLA; [FE]-HYDROGENASE; H2-EVOLUTION; HYDROGEN; FERREDOXIN